Thyroid status among critically ill patients admitted in the intensive care unit of the government tertiary care hospital in Mandya: a retrospective study - K. L., Chethan Kumar; K. M., Shivakumar (International Journal of Advances in Medicine, 2020)
Background: The nonthyroidal illness syndrome, also known as the low T3 syndrome or euthyroid sick syndrome. Any acute severe illness can cause abnormalities of circulating Thyroid Stimulating Hormone (TSH) or Thyroid Hormone (TH) levels in the absence of underlying thyroid disease. The laboratory parameters of this syndrome include low serum levels of T3 and high levels of reverse T3, with normal or low levels of thyroxine (T4) and normal or low levels of TSH. This condition may affect 60-70% of critically ill patients. The severity of illness correlates well with the reduction in total serum T3 level. Objectives of the study was to assess the thyroid status of critically ill patients admitted in intensive care unit of a tertiary care hospital. Methods: This is a retrospective observational study done at Department of General Medicine, MIMS, Mandya among patients admitted with critical illness to ICU. 100 patients admitted with critical illness to ICU are included in this study. Thyroid function reports obtained from case sheets, data entered into MS Excel sheet and analysed. Results: Out of 100 patients studied 34 patients had sepsis, 26 patients had respiratory failure, 20 patients had Congestive cardiac failure, 12 patients had acute renal failure and 8 patients had Diabetic ketoacidosis. Among 100 patients 63% had abnormal thyroid function test, 56% had low T3, 12% had low T4, 2% had high T4 and 3% had low TSH. Conclusions: Thyroid function abnormality suggesting Non thyroid illness or euthyroid sick syndrome is common among critically ill patients.